KURSUS SEPAK TAKRAW ASEAN - Achmad Sofyan Hanif; Burhan Basyiruddin; Abdul Gani; Jufrianis; Abdul Azis Hakim; Tri Aji (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2021)
Abstract This Community Service aims to improve the quality of Sepaktakraw trainers in the ASEAN region, with courses that are carried out continuously and continuously according to the needs of current Sepaktakraw trainers. Regeneration in the world of coaching needs to be continuously improved, especially in the sport of sepaktakraw, The implementation program will be carried out through seminars and workshops. If possible, it will be done in person; however, if it cannot be done through zoom cloud meetings. This community service is carried out in the ASEAN environment starting from May - October 2021. It is hoped that the results of community service carried out to these coaches can form good athletes and teams, so that competition between Sepaktakraw teams in Asean countries is more competitive. Abstrak Pengabdian kepada Masyarakat ini bertujuan untuk meningkatkan kualitas pelatih sepak takraw di kawasan ASEAN, dengan kursus yang dilakukan secara terus menerus dan berkesinambungan sesuai dengan kebutuhan pelatih sepak takraw saat ini. Regenerasi dalam dunia kepelatihan perlu terus ditingkatkan khususnya pada cabang olahraga sepaktakraw Program pelaksanaannya akan dilakukan melalui seminar dan workshop. Jika memungkinkan, itu akan dilakukan secara langsung; namun jika tidak bisa dilakukan melalui zoom cloud meeting. Pengabdian kepada masyarakat ini dilaksanakan di lingkungan ASEAN mulai bulan Mei – Oktober 2021. Hasil pengabdian masyarakat yang dilakukan kepada para pelatih ini dapat membentuk atlet dan tim yang baik, sehingga persaingan antar tim sepak takraw di negara-negara Asean lebih kompetitif.